Masā’il Da‘wiyyah fī Ẓāhirat Sabb al-Rabb wa al-Dīn fī al-Duwal al-‘Arabiyyah (Dirāsah Waṣfiyyah Taḥlīliyyah Muqāranah) - Hamdan, Mohd O. M.; Bin Ahmad Shah, Faisal (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
Cursing God and religion is a phenomenon that continues to spread in twelve Arab countries and urged to be resolved. This research aims to strengthen and improve the way to combat this phenomenon from the side of da'wah by outlining several issues, such as; the widespread confusion that hampers efforts to resolve this phenomenon in terms of da'wah, sharia law related to vigilantism to perpetrators of blasphemy of God and religion acted upon unemphatically by positive law, the reasons that cause people to gradually insult God and religion, and a comparison of the efforts of the two most prominent media outlets in each Arab country to find out whether they are carrying out their journalistic responsibilities. Using descriptive, analytical, and inductive methods, this study concludes that vigilante actions against perpetrators of blasphemy of God are prohibited because this is part of the verse that prohibits blasphemy. In addition, most popular media channels have played a less important role in resolving this phenomenon.